A snapshot look at replication and statistical reporting practices in psychology journals. Issue 2 (3rd July 2019) - Imam, Abdulrazaq A.; Frate, Melissa
ABSTRACT: Current efforts started in 2012 by the Association for Psychological Science (APS) appear to be different from previous arguments against null hypothesis statistical testing (NHST), which remained largely rhetorical without specific actions for compliance by researchers in psychology. The APS advocacy involves specific promising implementation tactics. The present study examined the impact of those efforts on replication and statistical reporting practices in four psychology journals from 2011 and 2015. The results showed that amidst increased reporting of NHST statistics in 2015 compared to 2011 and an absence of power reporting in the behavioral journals, there was increased reporting of actual replications in  Psychological Science, paradoxically surpassing  Journal of the Experimental Analysis of Behavior, of CIs in all four journals, and of error bars on graphs in  Cognition  and  Behavioural Processes . These trends suggest need for additional efforts at propagating the APS initiatives to ensure greater impact in the broader psychological community. Additionally, psychologists from all domains need to become advocates of best practices for sustainable impact.